Program Management Approach for Concurrently Managing Projects – A study from Khairun University - Johan Fahri; Muhammad Asril Arilaha; Rheza Pratama (AIBPM Publisher, 2020)
Complexity and uncertainty has led organizations to sustaining the strategic operations for future challenges. Project management is expected to uplift its scope in managing complex projects into strategic level. The study aims to offer a prospective angle in realizing organization’s goals by managing a number of small projects that are reached through a competition of limited resources within an organization. Program management is suggested as methodological paraphernalia, particularly in refining pathways of strengthening an organization, including a higher education institution such as Khairun University. The study demonstrated a solution to manage small and separated projects concurrently.